1977
DOI: 10.1159/000207898
|View full text |Cite
|
Sign up to set email alerts
|

B and T Cell Markers of Bone Marrow and Peripheral Blood Lymphoid Cells in Patients with Paraproteinaemia

Abstract: Studies have been carried out on B and T cells in bone marrow and peripheral blood from patients with paraproteinaemia. The peripheral blood of patients with multiple myeloma showed a significant increase of B cells, mainly lymphoid cells bearing immunoglobulins corresponding to the paraproteins, while in patients with benign monoclonal gammopathy only a slight increase of B cells and a moderate decrease of T cells have been found. As to the bone marrow, the B cell population was significantly raised in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
1991
1991

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…The patients were mostly older than the controls, but we have not found age to be a significant factor in receptor studies. Previous investigations of granulocyte function in patients with myelomatosis have demonstrated impairment due to serum or plasma factors (3,5 ) . Hopen et al (4) found myelomatosis serum to decrease granulocyte adhesion and migration; this effect could not, however, be correlated to the decreased phagocytosis by myelomatosis granulocytes, as measured by chemiluminescence.…”
Section: Discussionmentioning
confidence: 98%
“…The patients were mostly older than the controls, but we have not found age to be a significant factor in receptor studies. Previous investigations of granulocyte function in patients with myelomatosis have demonstrated impairment due to serum or plasma factors (3,5 ) . Hopen et al (4) found myelomatosis serum to decrease granulocyte adhesion and migration; this effect could not, however, be correlated to the decreased phagocytosis by myelomatosis granulocytes, as measured by chemiluminescence.…”
Section: Discussionmentioning
confidence: 98%